APPLICATION OF DESIGN THINKING METHOD TO THE INNOVATION BUSINESS DESIGN PROCESS OF AUTOMATIC AQUATIC PET FEEDER WITH IOT - Prima Imanuela Putri; Lely Dahlia (FEB-UP Press, 2023)
This study aims to apply the design thinking method to the process of designing an innovative Automatic Aquatic Pet Feeder with IoT business. This study focuses on discussing design thinking with four stages, namely empathize, define, ideate, and prototype. At the define stage there is a Business Model Canvas which has nine elements, starting from customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure which aims to provide a simpler business model representation. This study uses a qualitative descriptive research method. Collecting data in this study using questionnaires and interviews with a total of 97 respondents. The results of this study are that fish keepers are very interested in Automatic Aquatic Pet Feeder with IoT products and will facilitate decision-making both in terms of business innovation to the design of the product.